Exploring the limitations of the MacDonald '3 + 1' condensation in the preparation of porphyrins with fused electron-withdrawing heterocyclic rings: Synthesis of a bis(thiadiazolo)benzoporphyrin and a related benzocarbaporphyrin. Issue 48 (26th November 2020) - Cillo, Catherine M.; Geiger, Mark A.; Lash, Timothy D.
Graphical abstract: Abstract: A pyrrole ethyl ester with a fused bis(thiadiazolo)benzo unit was prepared by reacting 4-nitrobenzo[1, 2- c :3, 4- c' ]bis(1, 2, 5)thiadiazole with ethyl isocyanoacetate in the presence of a non-nucleophilic base. Cleavage of the ester moiety, followed by reaction with a chloromethylpyrrole in refluxing pyridine, afforded a tripyrrane and subsequent acid-catalyzed condensation with pyrrole or indene dialdehydes gave porphyrinoids incorporating fused electron-deficient heterocyclic units.